The Mediating Role of Trust in The Relationship Between Online Advertising and Purchase Decision in E-Commerce: A Study on Seblak Chips Products in Shopee - Santoso, Fuji; Sudarmiatin, Sudarmiatin (Asian Journal Science and Engineering, 2025)
The growth of e-commerce has transformed consumer shopping behavior, making online advertising a vital marketing tool. However, trust remains a critical factor in influencing consumer decisions in the digital marketplace. This study aims to examine the effect of online advertising on purchase decisions, with trust as a mediating variable. The research employed a quantitative method using a survey of 120 Shopee users who had purchased Seblak chips in the past three months. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings show that online advertising has a significant positive effect on trust, and trust significantly influences purchase decisions. Furthermore, trust mediates the relationship between online advertising and purchase decisions. These results imply that trust plays a pivotal role in enhancing the effectiveness of online advertising in e-commerce. Business owners should not only focus on creating attractive advertisements but also prioritize building consumer trust through transparent and consistent communication.